Canada Island (Seville Enterprises, Inc.)
Colorful Flags unfurled in front of the British Columbia Pavilion. Also on Canada Island is Alberta's outdoor amphitheater and inside viewing area. And for the children, a most unusual and enjoyable park and play area.